p53 regulates lysosomal membrane permeabilization as well as cytoprotective autophagy in response to DNA-damaging drugs - Yamashita, Gai; Takano, Naoharu; Kazama, Hiromi; Tsukahara, Kiyoaki; Miyazawa, Keisuke (Cell death discovery, 2022)
Lysosomes are single-membraned organelles that mediate the intracellular degradation of macromolecules. Various stress can induce lysosomal membrane permeabilization (LMP), translocating intralysosomal components, such as cathepsins, to the cytoplasm, which induces lysosomal-dependent cell death (LDCD). This study reports that p53 regulates LMP in response to DNA-damaging drugs. Treating wild-type TP53 A549 cells with DNA-damaging drugs (namely, doxorubicin, carboplatin, and etoposide) induced LMP and accelerated cell death more rapidly than treating TP53 -knockout (KO) A549 cells. This suggested p53-dependent LMP and LDCD induction in response to DNA damage. LMP was induced by p53-dependent BID upregulation and activation, followed by translocation of truncated BID to lysosomes. Simultaneously, autophagy for damaged lysosome elimination (lysophagy) was activated via the p53–mTOR–TEFB/TFE3 pathways in response to DNA damage. These data suggested the dichotomous nature of p53 for LMP regulation; LMP induction and repression via the p53–BID axis and p53–mTOR–TFEB/TFE3 pathway, respectively. Blocking autophagy with hydroxychloroquine or azithromycin as well as ATG5 KO enhanced LMP and LDCD induction after exposure to DNA-damaging drugs. Furthermore, lysosomal membrane stabilization using U18666A, a cholesterol transporter Niemann-Pick disease C1 (NPC1) inhibitor, suppressed LMP as well as LDCD in wild-type TP53 , but not in TP53 -KO, A549 cells. Thus, LMP is finely regulated by TP53 after exposure to DNA-damaging drugs.